Effect of Transplanting Dates and Training Systems on Fruit, Seed Yield and Quality Attributes in Tomato (Solanum Lycopersicum) Under Protected Conditions - MANISH KUMAR; SANTOSH GUPTA; PALAK SHARMA; SAILJA THAKUR (Seed Research, 2026)
The experiment was undertaken during kharif season of 2019-20, inside a plastic greenhouse atexperimental farm and laboratory conditions of department of Seed Science and Technology, Dr. Y S P Universityof Horticulture and Forestry, Nauni, Solan, H.P. in order to determine the effect of planting dates and trainingsystems on fruit, seed yield and quality in tomato cv. Solan Lalima. The treatments comprised of four plantingdates (transplanting on 1st April, 15th April, 1st May and 15th May) and four training systems (single stem, two stem,four stem, no training). The different treatments showed differential response but overall transplanting on 1st Aprilwith two stem training system was significantly superior or at par with best results for various yield and qualitytraits in tomato like number of flowers per cluster, number of fruits per cluster, fruit set percent, total number offruits per plant, average fruit weight, fruit yield, 1000 seed weight, number of seeds per fruit, seed yield, percentseed germination, seedling length, seedling dry weight, SVI-I & II, cold test and accelerated aging test. Hence, forhigher quality fresh fruit and quality seed produce, treatment combination comprising of transplanting on 1st Aprilwith two stem training system can be recommended for growing tomato under protected conditions on commercialscale in mid hills of Himachal Pradesh.